The Burden of Cancer, Government Strategic Policies, and Challenges in Pakistan: A Comprehensive Review - Ali, Anwar; Manzoor, Muhammad Faisal; Ahmad, Nazir; Aadil, Rana Muhammad; Qin, Hong; Siddique, Rabia; Riaz, Sakhawat; Ahmad, Arslan; Korma, Sameh A.; Khalid, Waseem; Aizhong, Liu (Frontiers in Nutrition, 2022)
Cancer is a severe condition characterized by uncontrolled cell division and increasing reported mortality and diagnostic cases. In 2040, an estimated 28.4 million cancer cases are expected to happen globally. In 2020, an estimated 19.3 million new cancer cases (18.1 million excluding non-melanoma skin cancer) had been diagnosed worldwide, with around 10.0 million cancer deaths. Breast cancer cases have increased by 2.26 million, lung cancer by 2.21 million, stomach by 1.089 million, liver by 0.96 million, and colon cancer by 1.93 million. Cancer is becoming more prevalent in Pakistan, with 19 million new cancer cases recorded in 2020. Food adulteration, gutkha, paan, and nutritional deficiencies are major cancer risk factors that interplay with cancer pathogenesis in this country. Government policies and legislation, cancer treatment challenges, and prevention must be revised seriously. This review presents the current cancer epidemiology in Pakistan to better understand cancer basis. It summarizes current cancer risk factors, causes, and the strategies and policies of the country against cancer.